Drafting international arbitration clauses - Ari D. MacKinnon; Ignacio Zapiola; Santiago Bravo (Thēmis, 2016)
This article offers an academic and practical overview for the drafting of international arbitration clauses, from an international Latin American approach and with special emphasis on the energy and construction industries.